A cannabis pricing mistake from California to Canada: government can't tax cannabis optimally. Issue 9 (21st May 2021) - Childs, Jason; Stevens, Jason
ABSTRACT: We apply a simple three good general equilibrium model to examine the optimality of a Pigouvian tax on a legal cannabis market which faces competition from a well-established illicit market. Despite the widespread support for Pigouvian taxes on cannabis, the availability of untaxed illicit cannabis with comparable costs and higher externalities renders taxation of legal cannabis suboptimal. Our results, derived from a relatively simple model, show that the welfare improving properties of a Pigouvian tax can be undermined by illicit market competition. Based on this simple analysis, we conclude that it is impossible for the pricing policies implemented in multiple jurisdictions (including California and Canada) to achieve the optimal, welfare maximizing outcome.